Experience of enrollment and management of the Waiting list for liver transplantation at hepatological center - Ye. N. Bessonova; O. A. Stroganova; Yu. A. Glazyrina; I. A. Kornilova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2013)
Aim of investigation. To carry out integrated analysis of the liver cirrhosis group of patients and indications for transplantation with evaluation of leading causes and factors affecting shifting liver transplantation in the Waiting list.Material and methods. All patients with liver cirrhosis admitted to the Sverdlovsk regional hepatological center in 2005 to 2010, were evaluated for option of inclusion to the Waiting list.Results. Most often alcoholism (21,6%) and cardiovascular diseases (14,0%) prevented inclusion to the Waiting list of potential recipient. These or other concomitant diseases become an impediment for enrollment to the waiting list in 2/3 patients having indications for liver transplantation.Conclusions. Development and management of the Waiting list for liver transplantation is a complex, multiplane task and requires careful, complex and very versatile investigation of the patient before surgery, dynamic rating of severity of status and urgency class of operation performance, duly while maximally effective detection and treatment of accompanying diseases.